(untitled) (Al Dzahab, 2026)
Purpose: This study aims to analyze the effect of job involvement, job characteristics, and organizational commitment on employee performance at the Housing, Settlement, and Land Affairs Office of Sungai Penuh City. Design/Methodology/Approach: This study employed a quantitative survey approach, distributing questionnaires to 49 employees. Data were analyzed using IBM SPSS 26.0 through validity and reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). Findings: The results reveal that job involvement, job characteristics, and organizational commitment partially have a positive and significant effect on employee performance. Simultaneously, all independent variables significantly influence employee performance, indicated by an F-test significance value of 0.000. The coefficient of determination (R²) of 0.722 indicates that the three variables explain 72.2% of the variance in employee performance, while other factors outside the research model explain 27.8%. Research Implications: The findings suggest that organizations, particularly public institutions, should strengthen employee involvement, improve job design, and enhance organizational commitment to achieve optimal and sustainable employee performance.